GDF-15 and Hepcidin Levels in Nonanemic Patients with Impaired Glucose Tolerance. (25th August 2016) - Yalcin, Mehmet Muhittin; Altinova, Alev Eroglu; Akturk, Mujde; Gulbahar, Ozlem; Arslan, Emre; Ors Sendogan, Damla; Yetkin, Ilhan; Toruner, Fusun Balos
Abstract : Aims . Growth Differentiation Factor-15 (GDF-15) has been suggested as one of the regulators of hepcidin, an important regulatory peptide for iron deposition. Current data is conflicting about the relationship between hepcidin and disorders of glucose metabolism. We aimed to investigate serum hepcidin and GDF-15 concentrations and their associations with each other, in nonanemic subjects with impaired glucose tolerance (IGT) in comparison with the nonanemic subjects with normal glucose tolerance (NGT). Methods . Thirty-seven subjects with IGT and 32 control subjects with NGT, who were age-, gender-, and body mass index- (BMI-) matched, were included in the study. Results . Serum GDF-15 levels were significantly higher in IGT compared to NGT. There were no differences in hepcidin, interleukin-6, and high sensitive C-reactive protein levels between the groups. We found a positive correlation between GDF-15 and hepcidin levels. There were also positive correlations between GDF-15 and age, uric acid, creatinine, and area under the curve for glucose (AUC-G). Hepcidin was correlated positively with ferritin levels. In the multiple regression analysis, GDF-15 concentrations were independently associated with age, uric acid, and AUC-G. Conclusions . Impaired glucose tolerance is associated with increased GDF-15 levels even in the absence of anemia, but the levels of hepcidin are not significantly altered in prediabetic state.